Investor reaction to IFRS for financial instruments in Europe: the role of firm-specific factors - Onali, Enrico; Ginesti, Gianluca; Ballestra, Luca Vincenzo (Elsevier, 2017)
We examine the market reaction to events related to the standard-setting process of International Financial Reporting Standard (IFRS) 9 for over 3,000 European firms that have adopted IFRS. We find that the market reaction to IFRS 9 is largely affected by firm-specific factors associated with information quality and information asymmetry. In particular, lower information asymmetry and higher information quality have a positive effect on market-adjusted returns. This is in conflict with the common view that IFRS 9 will improve accounting quality for those firms that need it most (namely, small firms with low liquidity and concentrated ownership structure).